EDUCATIONAL EFFORTS IN MANAGING NARCOTICS ABUSE PERSPECTIVE SANI (INDONESIAN ANTI-NARCOTICS CELEBRITIES) AND BNN (NATIONAL NARCOTICS AGENCY) - Sofian Syaiful Rizal; Deddy Junaedi (PEDAGOGIK : JURNAL PENDIDIKAN, 2021)
Narcotics abuse is still a serious threat in Indonesia, especially its use is very widespread by some of the public figures of the artists involved in it. So that it becomes a spotlight for young people, especially those whose lives are still unstable, seeing public figures as examples of current trends in the millennial world. The purpose of this study is to minimize and overcome the use of narcotics from various circles, both public figures, BNN, the Police, and the community. The problem approach used in this research is a normative juridical approach and an empirical juridical approach, namely an approach that is carried out through studies of theories, concepts, views, and aspects related to the problems discussed. The results of this study are the formation of teamwork in overcoming the use of narcotics both from all walks of life, especially for public figures (artists) by working together from various parties, both communities, agencies, BNN so that the younger generation of Indonesia is no longer touched by narcotics whose impact is very damaging the nation's young generation, both in socializing, achieving and living a normal life by maintaining akhlaqul karimah/etiquette in social life without narcotics.